Nonlinear pricing with self-control preferences - Susanna Esteban; Eiichi Miyagawa; Matthew Shum (The Johns Hopkins University, Department of Economics, 2003)
This paper studies optimal nonlinear pricing for a monopolist when consumers' preferences exhibit temptation and self-control as in Gul and Pesendorfer (2001a). Consumers are subject to temptation inside the store but exercise self-control, and those foreseeing large self-control costs do not enter the store. Consumers differ in their preferences under temptation. When all consumers are tempted by more expensive, higher quality choices, the optimal menu is a singleton, which saves consumers from self-control and extracts consumers' commitment surplus. When some consumers are tempted by cheaper, lower quality choices, the optimal menu may contain a continuum of choices.
Keywords: D42; D82; L12; L15; 330; Temptation; self-control; commitment; nonlinear pricing; price discrimination.; Betriebliche Preispolitik; Präferenztheorie; Preisdifferenzierung; Theorie